Effect of Supplementation of Calcium Propionate on Nutrient Digestibility and Milk Yield in Dairy Cattle - Ravi , Kumar D; MVAN, Suryanarayana; Devasena , B; Ravindra , Reddy Y; Maram, Harani (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Twenty-four lactating dairy cows randomly assigned to four treatments with each group containing six cows in a completely randomized design were evaluated to study the effect of supplementation of calcium propionate at different levels in combination with concentrate pellet feed, green fodder and paddy straw on nutrient digestibility, milk yield and milk composition parameters. The dietary treatments contained ad libitum APBN-1 green fodder, concentrate pellet feed and paddy straw. The treatments were a diet with no calcium propionate supplementation as T1 (control), T1 + 60g calcium propionate / animal / day (T2), T1 + 70g of calcium propionate / cow / day (T3) and T1 + 80g calcium propionate / cow / day (T4). A lactation trial of 40 days was conducted. At the end of lactation trial, a digestion trial was conducted to evaluate the effect of calcium propionate on nutrient utilization. The digestibility (%) of DM, OM, CP, EE, CF and NFE were found to be significant (P< 0.05) among treatments. The digestibility coefficient values were 60.52, 62.81, 63.19 and 64.14 for DM; 61.13, 63.67, 63.87 and 64.41 for OM; 60.91, 64.92, 65.12 and 65.64 for CP; 74.02, 75.68, 76.19 and 74.78 for EE; 41.90, 45.99, 46.23 and 46.63 for CF and 64.14, 68.58, 69.08 and 69.88 for NFE for T1 to T4 fed cows with calcium propionate, respectively. The digestibility (%) of cell wall fractions was 65.86, 67.42, 66.64 and 68.42 for NDF; 54.35, 58.42, 57.64 and 58.46 for ADF for T1, T2, T3 and T4 fed cattle, respectively. The values for ADF and NDF were non-significant. Average dry matter intake (kg/day) 9.98 ,10.34, 10.27 and 10.45 for T1, T2, T3 and T4, respectively. The feed conversion ratio in terms of milk yield was 2.31, 2.27, 2.29 and 2.16 for T1, T2, T3 and T4 where T4 fed group was recorded lowest feed conversion value when compared among the groups, further indicating an increasing trend in dry matter intake thereby increase in milk yield eventually. It was concluded that supplementation of higher dose of calcium propionate improved the nutrient digestibility and milk yield than middle and lower levels.
Keywords: calcium propionate; digestibility, milk yield; FCR in ruminants